2019
DOI: 10.1101/748814
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Alzheimer’s disease associated bacterial protease RgpB from P. gingivalis activates the alternative β-secretase meprin β thereby increasing Aβ generation

Abstract: Alzheimer's disease (AD) is the most common type of dementia and characterized by tau hyperphosphorylation, oxidative stress, reactive microglia and amyloid-β (Aβ) deposits. A recent study revealed that Porphyromonas gingivalis infection is associated with amyloid β generation in Alzheimer's disease. Increased Aβ levels, tau degradation and neuronal toxicity were observed as a consequence of ginigipain R (RgpB) activity, a cysteine protease constitutively secreted by P. gingivalis. Of note, we previously ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In contrast to Ca 2+ , which stabilizes enzyme activity, glycyl-glycine considerably enhances the inactivation rate. RgpB shows proteolytic activity towards APP resulting in degradation of soluble APP ectodomains generated by βand γ-secretases [30]. RgpB is capable of destroying human connective tissues, cell surface proteins and receptors, cytokines, components of the coagulation and complement cascades, heme and iron-binding proteins, immunoglobulins, and proteinase inhibitors as a result of the aforementioned situation [150].…”
Section: Rgpb Gingipainmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Ca 2+ , which stabilizes enzyme activity, glycyl-glycine considerably enhances the inactivation rate. RgpB shows proteolytic activity towards APP resulting in degradation of soluble APP ectodomains generated by βand γ-secretases [30]. RgpB is capable of destroying human connective tissues, cell surface proteins and receptors, cytokines, components of the coagulation and complement cascades, heme and iron-binding proteins, immunoglobulins, and proteinase inhibitors as a result of the aforementioned situation [150].…”
Section: Rgpb Gingipainmentioning
confidence: 99%
“…Epidemiological studies show correlations between AD and periodontitis, an oral disease in which P. gingivalis plays a central role [28]. Various preclinical studies have shown the presence of P. gingivalis to lead to AD cerebral pathologies and cognitive decline [29][30][31]. Recently, traces of this pathogen were discovered in brain legions of AD patients, providing evidence for a possible causal relationship [32].…”
Section: Introductionmentioning
confidence: 99%
“…The protected hydroxamic acid was introduced by coupling of 11 with benzylhydroxylamine. The formation of the pyrazole core was accomplished using a one-pot method reported by Heller et al 39 The 1,3-diketone intermediates were synthesized from the N-benzyloxy-4oxo-4-phenylbutanamide derivatives (12) and either acid chlorides or carboxylic acids and carbonyldiimidazole. The 1,3-diketones were converted in situ into the respective pyrazoles (13 & 14) by subsequent addition of hydrazine monohydrate.…”
Section: Synthesismentioning
confidence: 99%
“…Meprin α is supposed to act as promigratory protease in the context of colorectal and hepatocytic cancer [1][2][3][4][5][6] and was also linked to vascular diseases like arteriosclerosis, cardiac remodeling and aneurysms, recently [7][8][9] . Meprin β is also involved in cancer cell invasion 10,11 and moreover is able to act as an alternative beta-secretase, contributing to the progression of Alzheimer´s disease via the release of neurotoxic amyloid peptides [12][13][14][15][16][17] . Both proteases act as procollagenases and are involved in the biosynthesis and assembly of collagen fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…Sophie’s research found the presence of LPS P. gingivalis in the brains of Alzheimer’s patients 3 . The mechanism for invading P. gingivalis bacteria into brain tissue is by penetrating the blood-brain barrier and damaging neuron cells 4 . When entering the central nervous system, these bacteria will first activate defense cells in the brain, namely the microglia, and astrocytes.…”
Section: Introductionmentioning
confidence: 99%